Natural Disasters - Makna Sabardalam Konteks Ketahanan Korban Banjir - Arif Chasanul Muna; Achmad Baihaqi; Muhamad Muhlisin (JURNAL PENELITIAN, 2016)
The principal problem in this research includes two things: how does the understanding and implementation of the flood victims in Pasirsari village toward the concept of patience, and what is the process of understanding to the formation and implementation of such forbearance in the context of socio-cultural and religious life in Pasirsari. This research is a field research using qualitative methods. Qualitative methods are used to describe the understanding of the flood and how the formation process occurs. The analysis used is descriptive-evaluative analysis, followed by explanatory analysis, critical analysis, and comparative analysis. Among the results of this study, flood victims are identified as having three aspects of patience, namely ahwal, aqwal, and af‘al. Thus, the internal act aspect of people only covers ahwal, while external aspects cover speech (aqwal) and action (af‘al).